Empowering Students in Lifelong Learning: Forging a New Practice of VPL in Icelandic Universities (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This essay examines the expansion of VPL into Icelandic universities, highlighting a collaborative initiative among the University of Iceland, University of Akureyri, University of Reykjavík, and Iceland University of the Arts. The paper presents the project, focusing on the strategy developed between the universities for similar, transparent validation processes, partly based on the experience gained in VPL in preschool teacher studies at the University of Iceland. The author discusses the benefits of VPL, such as increased educational accessibility, alignment with labor market needs, and the promotion of lifelong learning. It underscores VPL’s potential to transform university education by valuing experiential and informal learning, thus promoting a more equitable and dynamic academic landscape. In addition, the paper outlines benefits and challenges, as well as innovations involving VPL at the university level in Iceland.